Optimization of solution heat exchanger of AHP in flue gas waste heat recovery. (2017) - Niu, Yang; Hua, Jing; Fan, Hongming
Abstract: Latent heat recovery is a significant issue in heat recovery of nature gas, and it can improve thermal efficiency of boilers greatly. A scheme involving AHPs (absorption heat pumps) to generate cold water to recover latent heat in flue gas is proposed and applied to northern China. COP of AHPs is greatly affected by solution HXs (heat exchangers), so performance of the HX cannot be too low. In the article, a new system is put forward, investment of solution heat exchanges can be decreased greatly. Afterwards, key parameters and investment saving ratio are discussed. Optimal flue gas temperature drop in flue gas-solution HXs is calculated and maximum of investment saving ratio is put forward.